Nitrification and Denitrification of Partially Treated Landfill Leachate - Abdul Wahid, Manisya Zauri (2004)
In this study, biological removal of ammonia, nitrite and nitrate nitrogen of partially treated landfill leachate (PTLL) was conducted by nitrification and denitrification processes. The experiments were conducted by batch treatment using 16L stirred tank reactor in which 8 L of PTLL was treated with O%, I%, 5% and 10% (vlv) of centrifuged landfill Ieachate sludge and the pH was adjusted to 7 at every 12 hour interval. The treatment systems were kept above 80% saturated with oxygen (0.06- 0.19 vvm). It was found that the treatment with 10% centrifuged landfill leachate sludge was sufficient to reduce 93% and 63% of the PTLL7s ammonia and nitrite, respectively, under aerobic condition. It was also observed that the level of nitrate can be reduced by 56% by biological means from the PTLLYs original concentration of 13,500 ppm during nitrification process. However, subsequent denitrification was not possible due to foaming which occurred during the nitrification treatment with 10% centrifbged landfill leachate sludge. Large loss of biomass from the system was experienced, even when the flowrate of air supplied was reduced to a very low level at 0.06 vvm. Furthermore, the impeller located at the upper part of the reactor's shaft was unable to break the large amount of foam formed. As an alternative to prevent foaming, further experiments were carried out in a 6L reactor with the use of 4L synthetic media of (a) defined media with controlled pH between 7.5 and 8.5; (b) model leachate (without organic nitrogen) with (i) pH adjusted to 7 every 12 hours (ii) controlled pH between 7.5 and 8.5; and (c) model leachate (with organic nitrogen and pH controlled between 7.5 and 8.5. These media consisting of ammonia, nitrite and nitrate concentrations of 1000 ppm, 1500 ppm and 3000 ppm, respectively, were treated with 10% of centrifuged landfill leachate sludge for complete nitrification and denitrification processes and to isolate the microbes involved. The saturated oxygen was kept above 80% (0.02 vvm) throughout the treatments. Complete nitrification and denitrification were achieved at 120 and 168 hours, when defined media and model leachate (without organic nitrogen) were used respectively, under controlled pH between 7.5 and 8.5. The cell population of both treatments was found to increase from lo8 to 10" cell/ml and lo9 to 10" celllml respectively, at the end of denitrification process, under CM ratio of 0.4 in which acetic acid was used as carbon source.Several strains were isolated from nitrification and denitrification processes. They were strains WNZ 1, WNZ 2 and WNZ 3 (ammonia oxidizers) which were unable to be identified by Biolog Identification System, Acinetobacter calcoaceticus and Acidovorax konjaci (nitrite oxidizers) and Pseudomonas aeruginosa I, Pseudomonas aeruginosa 2 and Pseudomonas aeruginosa 3 (nitrate oxidizers).